Mini-Review: Antibiotic-Resistant Escherichia coli from Farm Animal-Associated Sources - Chunming Xu; Lingqiang Kong; Yonghong Liao; Yuan Tian; Qi Wu; Haosi Liu; Xiumin Wang (MDPI AG, 2022)
Escherichia coli is one of the most frequent causes of gastro-intestinal and extra-intestinal diseases in animals and humans. Due to overuse and misuse of antibiotics, recent years have seen a rapidly increasing prevalence of antibiotic-resistant (AR) Escherichia coli globally; particularly, AR E. coli from farm animal-associated sources and its antibiotic resistance genes (ARGs) are becoming a global concern, with clinical negative effects on both human and animal health. The aim of this review was to explore the prevalence trends of AR E. coli from farm animals, waste treatment, and aquatic environments. The disinfection methods of AR E. coli and possible alternatives to antibiotics were also highlighted. The current review highlights that the prevalence of AR E. coli from food animals, products, and animal waste is increasing at an alarming rate, but is reduced at waste treatment plants. Ultraviolet (UV) treatment, surface plasma oxidation, and biochar are commonly used to effectively eliminate AR E. coli. Some probiotics, plant extracts, and antimicrobial peptides (AMPs) are arousing interest as promising alternatives to antibiotics to fight against AR E. coli. The current review suggests that AR E. coli from farm animal-associated sources is prevalent and poses a serious global threat to public health. This review provides an avenue for further research, development, and application of novel strategies to minimize antibiotic resistance in E. coli of farm animal origin.